Peningkatan Pemahaman Keselamatan dan Penggunaan Peralatan Laboratorium Kimia Melalui Pembelajaran Praktis - Siska Alvionita; Triliyansi, Triliyansi; Asi, Nopriawan Berkat (Jurnal Ilmiah Kanderang Tingang, 2025)
This study aims to evaluate the effectiveness of practical learning activities in the chemistry laboratory of Palangka Raya University on increasing the understanding of SMAN 2 Kahayan Tengah students regarding the safety and use of chemistry laboratory equipment. This study uses a pre-experimental design with a one-group pretest-posttest approach. Grade XI students who participated in practical learning activities included the delivery of laboratory safety materials, introduction to laboratory tools and instruments, and demonstrations of simple chemical experiments. Student comprehension data was collected through pretest and posttest, then analyzed using the Wilcoxon signed-rank test and N-gain calculation. The results showed a significant increase (p < 0.05) between pretest scores (mean = 62.00) and posttest (mean = 80.33), with an average N-gain value of 0.48 which was included in the medium category. The conclusion of this study is that practical learning activities in the chemistry laboratory of the University of Palangka Raya are effective in improving the understanding of SMAN 2 Kahayan Tengah students regarding the safety and use of chemistry laboratory equipment.